2020
DOI: 10.1016/j.asmr.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Anterior Cruciate Ligament Length and Femoral Epicondylar Width Measured on Preoperative Magnetic Resonance Imaging or Radiograph

Abstract: Purpose: To determine whether femoral epicondylar width (FECW) obtained from either magnetic resonance imaging (MRI) or plain radiographs could be used to predict anterior cruciate ligament (ACL) length. A secondary purpose was to develop a formula to use maximum FECW on either MRI or plain radiographs to estimate ACL length preoperatively. Methods: The MRIs and radiographs of 40 patients (mean age 41.0 years), with no apparent knee pathology, surgery, or trauma were included. The ACL length was measured on MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Additionally, many consider the intra-articular distance of the ACL, not the patellar tendon length, as the most integral parameter to when attempting to mitigate graft-tunnel mismatch. However, the ACL is an obliquely oriented structure that cannot be easily measured with a single sagittal image 31 or requires complex formulas for accurate measurement 32 ; therefore, identifying more easily measured structures such as patellar tendon length and TT-TG would be a more reproducible source of information if a correlation did exist. In addition, accurate preoperative knowledge of patellar tendon length affords the surgeon with valuable information that may indicate the need for longer tibial tunnels, rotation of the graft, or other strategies necessary to circumvent graft-tunnel mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many consider the intra-articular distance of the ACL, not the patellar tendon length, as the most integral parameter to when attempting to mitigate graft-tunnel mismatch. However, the ACL is an obliquely oriented structure that cannot be easily measured with a single sagittal image 31 or requires complex formulas for accurate measurement 32 ; therefore, identifying more easily measured structures such as patellar tendon length and TT-TG would be a more reproducible source of information if a correlation did exist. In addition, accurate preoperative knowledge of patellar tendon length affords the surgeon with valuable information that may indicate the need for longer tibial tunnels, rotation of the graft, or other strategies necessary to circumvent graft-tunnel mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…Fayad et al studied gender differences in ACL and PCL volumes and showed that gender differences in ACL volume are present, but may be accounted for height differences between males and females [ 42 ]. The mean ACL length reported by Van Zyl et al was 40.6 mm in subjects with no apparent knee pathology, surgery, or trauma [ 44 ]. In our study, we observed a mean ACL length of 35.2 mm for patients with meniscal tears and 33.9 for end-stage OA patients).…”
Section: Discussionmentioning
confidence: 99%
“…Sagittal proton density‐weighted scans taken from the tibial tubercle to 10 cm proximal to the proximal patellar pole using 3‐mm slices were obtained, and the length of the QT was measured from the superior pole of the patella to the musculotendinous junction of the rectus femoris on the slice in which the longest tendon was seen. The ACL was imaged using multi‐slice planes to visualize both the femoral and tibial insertions, and the distance between the mid‐portion of the insertion sites was measured as the ACL length [3, 39]. The thickness of the QT and PT was measured at a site 3 cm from the patellar attachment [40] (Fig.…”
Section: Methodsmentioning
confidence: 99%